2017
DOI: 10.3389/fcimb.2017.00362
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Leptospires Modulate Protein Expression and Post-translational Modifications in Response to Mammalian Host Signals

Abstract: Pathogenic species of Leptospira cause leptospirosis, a bacterial zoonotic disease with a global distribution affecting over one million people annually. Reservoir hosts of leptospirosis, including rodents, dogs, and cattle, exhibit little to no signs of disease but shed large numbers of organisms in their urine. Transmission occurs when mucosal surfaces or abraded skin come into contact with infected urine or urine-contaminated water or soil. Whilst little is known about how Leptospira adapt to and persist wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 70 publications
1
40
0
1
Order By: Relevance
“…At this time, a lymphocyte-rich inflammatory infiltrate in association with leptospires in infected kidney sections was apparent; however, it was also apparent that leptospiral organisms were also detected within tubules devoid of any immune response. It remains unclear if such responses can ultimately be successful enough to remove organisms and eliminate renal excretion, or whether leptospires can continue to evade detection and reactivity as hypothesized by differential expression of antigens (Nally et al, 2007 , 2011 , 2017 ; Monahan et al, 2008 ; Witchell et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this time, a lymphocyte-rich inflammatory infiltrate in association with leptospires in infected kidney sections was apparent; however, it was also apparent that leptospiral organisms were also detected within tubules devoid of any immune response. It remains unclear if such responses can ultimately be successful enough to remove organisms and eliminate renal excretion, or whether leptospires can continue to evade detection and reactivity as hypothesized by differential expression of antigens (Nally et al, 2007 , 2011 , 2017 ; Monahan et al, 2008 ; Witchell et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rat kidneys were harvested at approximately 8 weeks post-infection and immediately fixed by immersion in neutral buffered 10% formalin, processed routinely, embedded in paraffin, cut into 4 μm sections, and stained with hematoxylin and eosin (HE). Immunohistochemistry was performed on paraffin-embedded tissue sections using antiserum generated against outer membrane vesicles (OMV) of Leptospira species or with anti-LipL32 (Nally et al, 2004 , 2017 ). After dewaxing, tissue sections were blocked with 10% normal goat serum in PBS for 30 mins at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then following mass spectrometry analysis of proteins separated by 2-D gel electrophoresis, they showed that LoA22, an outer lipoprotein important for virulence, LipL32, LipL41 and chaperone proteins, are more abundant in vivo. In addition, these proteins were identified to have post-translational modifications, such as phosphorylation or tri-methylations, not observed in vitro when leptospires were grown in EMJH culture medium at 30 C or 37 C [30]. Therefore, PTM of leptospiral proteins may constitute a hurdle to generate effective vaccines from in vitro cultured bacteria, since candidate proteins will be devoid of these modifications and the antibodies elicited may not recognize the corresponding modified proteins expressed in the host.…”
Section: Post-translational Modificationsmentioning
confidence: 99%
“…Recently, Nally et al. reported that pathogenic leptospires modulate protein post-translational modifications in response to mammalian host signals [18] .…”
Section: Discussionmentioning
confidence: 99%